Nonthermal emission model of isolated X-ray pulsar RX J0420.0-5022 - Chkheidze, N.; Babyk, Iu. (Advances in Astronomy and Space Physics, 2013)
In this paper, an alternative theoretical interpretation to the generally assumed thermal emission models of the observed X-ray spectrum of isolated pulsar RX J0420.0-5022 is presented. It is well-known that at a pulsar surface, the distribution function of relativistic particles is one-dimensional. However, cyclotron instability causes an appearance of transverse momenta of relativistic electrons, which as a result start to radiate in the synchrotron regime. On the basis of the Vlasov kinetic equation we study the process of quasi-linear difusion (QLD) developed by means of the cyclotron instability. This mechanism enables the generation optical and X-ray emissions on the light cylinder lengthscales. An analysis of the three archival XMM-Newton observations of RX J0420.0-5022, is performed. Considering a different approach to synchrotron emission theory, a spectral energy distribution was obtained, which was in a good agreement with the observational data. A fit to the X-ray spectrum was conducted using both the present synchrotron emission model spectrum absorbed by cold interstellar matter, as well as the generally assumed black-body absorption model.